STATELINE. STATE HEADLINES. (Tufts Archival Research Center, 2007)
Compilation of headlines and summaries of legislative events from across the states. Focuses on taxes, fire-safe cigarettes, smoking restrictions, sampling/advertising/sales restrictions, employment discrimination, and local smoking restrictions.